Modeling the Chemical Enrichment History of the Bulge Fossil Fragment Terzan 5 - Donatella Romano; Francesco R. Ferraro; Livia Origlia; Simon Portegies Zwart; Barbara Lanzoni; Chiara Crociati; Davide Massari; Emanuele Dalessandro; Alessio Mucciarelli; R. Michael Rich; Francesco Calura; Francesca Matteucci (The Astrophysical Journal, 2023)
Terzan 5 is a heavily obscured stellar system located in the inner Galaxy. It has been postulated to be a stellar relic, a bulge fossil fragment witnessing the complex history of the assembly of the Milky Way bulge. In this paper, we follow the chemical enrichment of a set of putative progenitors of Terzan 5 to assess whether the chemical properties of this cluster fit within a formation scenario in which it is the remnant of a primordial building block of the bulge. We can explain the metallicity distribution function and the runs of different element-to-iron abundance ratios as functions of [Fe/H] derived from optical-infrared spectroscopy of giant stars in Terzan 5 by assuming that the cluster experienced two major star formation bursts separated by a long quiescent phase. We further predict that the most metal-rich stars in Terzan 5 are moderately He-enhanced, and we predict a large spread of He abundances in the cluster, Y ≃ 0.26–0.335. We conclude that current observations fit within a formation scenario in which Terzan 5 originated from a pristine or slightly metal-enriched gas clump about one order of magnitude more massive than its present-day mass. Losses of gas and stars played a major role in shaping Terzan 5 the way we see it now. The iron content of the youngest stellar population is better explained if the white dwarfs that give rise to type Ia supernovae (the main Fe factories) sink toward the cluster center, rather than being stripped by the strong tidal forces exerted by the Milky Way in the outer regions.